Capabilities of digital servitization: Evidence from the socio-technical systems theory - Münch, Christopher; Marx, Emanuel; Benz, Lukas; Hartmann, Evi; Matzner, Martin (Technological Forecasting and Social Change, 2022)
Driven by pressures for sustainable development and disruptions such as the COVID-19 pandemic, manufacturing companies in the 21st century are affected by two intertwined trends: Industry 4.0 and servitization. Digital servitization, which represents the transition from providing products to offering smart product-service systems, is currently seen as a black box by companies confronting them with major challenges. Current literature has not yet investigated which capabilities are required for the development and provision of smart PSSs. To address this gap, an exploratory multiple case study was performed using semi-structured interviews with 18 representatives of four manufacturing companies and six representatives of companies in a supporting role. A socio-technical systems perspective was adopted to cover the interconnectedness and complementarity of internal and external elements relevant for providing a smart PSS. The study identified 46 capabilities of digital servitization to offer and perform smart PSSs and systemically classified these within the dimensions of the socio-technical systems theory, thus providing companies with numerous insights into successful digital servitization. The results contribute to the practical and academic understanding of digital servitization by outlining capabilities to offer and perform smart PSSs and providing support for the use of socio-technical systems theory to frame these capabilities systematically.
Keywords: Digital servitization; Industry 4.0; Smart product-service system; Smart PSS; Manufacturing

Collaborative Partnerships - Conceptualization of Strategic Alliances for Sustainable Supply Chains - Münch, Christopher; Benz, Lukas (Academy of Management Proceedings, 2022)
To achieve sustainability among supply chain partners, many actors along the supply chain are increasingly engaging in strategic alliances. This paper aims to create an overview of the phenomenon of alliances and the underlying behavior of the participants leading to collaborative partnerships. Based on a literature review, a framework for strategic alliances that address sustainability issues in the supply chains of member companies is conceptualized. Findings suggest motives, interdependence, and implementation as central aspects for the overview of alliances. It revealed that the motives for participating in an alliance mainly lay on efficiency through shared resources and organizational learning, as well as institutional pressure. Drawing on the social exchange theory, aspects such as reciprocity, trust, commitment, and power can be promoted through the organization of the governance structure, fair allocation of power and benefits, and communication. To reduce issues due to information asymmetry, the implementation relies on tools, practices, and structured information exchange. This research contributes to filling identified gaps and expanding knowledge about the phenomenon of alliances to improve collaborative partnerships. It combines previous findings and creates a framework that provides an overview of the topi
Keywords: Agency theory; Institutional theory; Resource-based view; Social exchange theory; Supply chain collaboration; Sustainability

Critical Success Factors for Circular Business Model Innovation from the Perspective of the Sustainable Development Goals - Benz, Lukas (Sustainability, 2022)
Circular business-model innovation offers a path for the transformation of companies, enhancing resource productivity and efficiency, while also contributing to sustainable development. These fundamental changes in business are accompanied by a variety of challenges and barriers. To support companies on their journey, only a few studies have investigated the critical success factors for circular business model innovation through literature analysis. To contribute to this research, in this study, a methodological approach, mainly based on expert interviews, is proposed to gain in-depth insight into critical success factors for circular business model innovation. As a result, a framework covering critical success factors for circular business model innovation is developed, comprising nine top-codes and 37 sub-codes, and an analysis of each factor’s contribution to the UN’s Sustainable Development Goals is performed. The study thereby extends the theoretical basis for further research on circular business model innovation, as well as identifying their practical implications.
CRIS-Team Scopus Importer:2022-06-03
Keywords: circular economy; expert interviews; innovation; SDGs; sustainable production and consumption

Development of a search and rescue framework for maritime freight shipping in the Arctic - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Transportation Research Part A-Policy and Practice, 2021)
In recent years, Arctic routes have been receiving increasing attention, as they offer a solution to capacity bottlenecks on the most frequented routes, such as the Suez Canal, Strait of Malacca, and Panama Canal. Due to climate change and melting polar ice, Arctic routes, especially the Northern Sea Route/Northeast Passage and Northwest Passage, are becoming increasingly competitive. The consequence of this development is an increase in maritime traffic in Arctic waters. Due to the harsh environment, maritime activities in the Arctic are associated with numerous risks, as reflected in the 512 incidents in the last decade. Therefore, sufficient search and rescue capabilities are necessary to ensure safety. Thus far, various studies have focused on different components of search and rescue, such as port infrastructure, icebreaker capabilities, and navigation. However, there is no study offering a framework for the required further development of search and rescue capabilities. Therefore, in this paper, a search and rescue framework is proposed. The development of the framework is based on a literature review of dimensions of search and rescue in the Arctic. Semi-structured interviews with 24 experts regarding the identified dimensions were conducted. The results of the qualitative content analysis show a total of 23 top-codes and 50 subcodes, which are presented and discussed. The discussion leads to the presentation of the search and rescue framework, including the dimensions port infrastructure, search and rescue equipment, communication technology, navigation technology, standards and agreements, and cooperation and the respective top-codes. Finally, limitations are addressed, and starting points for further research are proposed.<br
Keywords: Arctic shipping; Northern Sea Route; Northwest Passage; Freight shipping; Search and rescue

Exploring the circular economy paradigm: A natural resource-based view on supplier selection criteria - Münch, Christopher; Benz, Lukas; Hartmann, Evi (Journal of Purchasing and Supply Management, 2022)
The paradigm of circular economy and the transfer of its principles to supply chain management has recently received much attention from researchers and practitioners. Limited natural resources, governmental legislation, and social responsibility for environmental preservation are the main factors for the development of circular supply chains. Especially in the automotive industry, critical materials are used to produce electric vehicles, reinforcing the importance of circularity for the industry. As the first stage of the supply chain, suppliers have a considerable influence on creating self-sufficient production systems, and in the automotive sector, a low level of vertical integration is important. Therefore, selecting suppliers is an enabler for circular supply chains, but this decision is a complex process due to multiple, partly conflicting criteria. To contribute to the knowledge in this research area, this study applies a fuzzy decision-making trial and evaluation laboratory approach for supplier selection in a circular supply chain in a case study of electric vehicles. First, a set of criteria for supplier selection in circular supply chains was identified based on a literature review and was systematically categorized based on the natural resource-based view. Afterward, the criteria were assessed and refined by experts with a strong procurement background in the automotive industry. Second, the experts were interviewed for value collection, and finally, the mutual influence of the criteria was determined. The results show that the most important criteria for circular supplier selection in electric vehicle supply chains are environmental standards, environmental-related certifications, resource consumption, and waste generation. Regarding the natural resource-based view, short-term focused criteria addressing the capability of pollution prevention have a higher importance compared to long-term criteria that drive sustainable development. In addition, this study classifies the criteria into the categories of causes and effects, discusses the prominence of the criteria, and presents a strategic map showing the mutual influences of the criteria. The results contribute to the theoretical and practical discussion on circular supply chains by identifying the key criteria for circular supplier selection and providing decision-making support for procurement managers.
Keywords: Automotive industry; Circular supply chain; Fuzzy DEMATEL; Multi-criteria decision-making (MCDM); Natural resource-based view; Supplier selection

Fuzzy-based decision analysis on Arctic transportation: A guidance for freight shipping companies - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability, 2021)
Purpose: Due to climate change the Arctic ice is melting, opening new possibilities for the economical use of the Arctic Ocean. However, the decision for shipping companies to transport freight through Arctic waters is based on many factors. The aim of the research is to develop a decision-supporting guidance for shipping companies. Methodology: Based on a literature review and subsequent validation through expert interviews, influencing factors are identified and classified using a framework covering Benefits, Opportunities, Costs, and Risks. A fuzzy set theory to structure multi-criteria decision problems is applied afterward. Findings: The results show that equipment, insurance, and inadequate port infrastructure are the factors with the highest influence in the Costs category and are the most influential factors overall. Security and market potential, the factors with the greatest impact on the Opportunities category, also rank highly as influential overall factors. The strongest Risk factors are weather conditions, delay, and collisions/accidents. The highest influence in the Benefits category are reduced costs. Originality: The influencing factors for Arctic freight shipping have so far only been considered in part with risks focus or other specific aspects, but not in the overall context. To consider multiple perspectives, 24 experts from different domains were involved.
CRIS-Team Scopus Importer:2024-12-16

Fuzzy-based decision analysis on Arctic transportation: A guidance for freight shipping companies - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Proceedings of the Hamburg International Conference of Logistics, 2021)
Purpose: Due to climate change the Arctic ice is melting, opening new possibilities for the economical use of the Arctic Ocean. However, the decision for shipping companies to transport freight through Arctic waters is based on many factors. The aim of the research is to develop a decision-supporting guidance for shipping companies. Methodology: Based on a literature review and subsequent validation through expert interviews, influencing factors are identified and classified using a framework covering Benefits, Opportunities, Costs, and Risks. A fuzzy set theory to structure multi-criteria decision problems is applied afterward. Findings: The results show that equipment, insurance, and inadequate port infrastructure are the factors with the highest influence in the Costs category and are the most influential factors overall. Security and market potential, the factors with the greatest impact on the Opportunities category, also rank highly as influential overall factors. The strongest Risk factors are weather conditions, delay, and collisions / accidents. The highest influence in the Benefits category are reduced costs. Originality: The influencing factors for Arctic freight shipping have so far only been considered in part with risks focus or other specific aspects, but not in the overall context. To consider multiple perspectives, 24 experts from different domains were involved.<br
CRIS-Team Scopus Importer:2024-12-16

Sustainable development through cross-company collaboration: an automotive case study of alliance phenomenon - Benz, Lukas; Münch, Christopher; Hartmann, Evi (Production and Operations Management Society (POMS), 2021)
In global supply chains, particularly at the bottom of the pyramid in emerging countries, sustainable development is a daunting challenge. Therefore, cross-company alliances are formed to enhance sustainability. Aim of this research is to analyze alliances based on an ellaborated framework by conducting a case study within the automotive industry.<br

Towards Sustainable Freight Transportation - A Risk Framework Application to Truck Platooning - Münch, Christopher; Benz, Lukas; Hartmann, Evi (Logistics Management, 2021)
National and international authorities, specifically the European Commission, have set challenging targets for the reduction of carbon emissions. Transportation is an important lever for emission reduction due to the share of over one quarter of the total emissions in Europe. In particular, road transportation, which accounts for 75% of the transported goods, offers saving potential. The improvement of traffic flows has been identified as a field for prospective energy consumption reduction, among others, by automation, especially platooning. Truck platooning has been discussed from a technical perspective, as well as with a focus on advantages. Risks have so far been included by some authors but not examined holistically. To close this research gap, a case study was conducted in this article to investigate the risks associated with platooning. For this purpose, eight semi-structured interviews were conducted with experts from logistics service providers and truck manufacturers. Eighteen risks were identified and classified into six dimensions (economic, social, legal, IT-related, technical, and ecological), resulting in a risk framework. The results extend the research on truck platooning by clarifying the risk perspective of this concept and provide a starting point for a discussion on the feasibilit